PROVERBS AND SAYINGS AS A SOURCE OF CULTURE IN LANGUAGE - Seytimbetova Aykumar Pulatbaevna (TADQIQOTLAR, 2026)
Annotation: This article explores proverbs and sayings as an essential source of cultural knowledge in the English language. Proverbs and sayings are examined as fixed expressions that reflect the historical experience, moral values, and worldview of a people. The study analyzes their linguistic features, classification, semantic structure, and cultural significance. Special attention is paid to the works of prominent linguists such as V.V. Vinogradov, A.V. Koonin, N.N. Amosova, and I.V. Arnold, whose theories contributed significantly to the understanding of phraseology. The article also provides examples illustrating how proverbs and sayings convey cultural norms, social behavior, and collective wisdom. It concludes that proverbs and sayings serve as valuable linguistic tools for preserving and transmitting cultural identity across generations.